2008
DOI: 10.3354/dao01886
|View full text |Cite
|
Sign up to set email alerts
|

Natural aquatic insect carriers of Macrobrachium rosenbergii nodavirus (MrNV) and extra small virus (XSV)

Abstract: Five different species of aquatic insects were collected from nursery ponds containing the freshwater prawn Macrobrachium rosenbergii infected with Macrobrachium rosenbergii nodavirus (Mr NV) and extra small virus (XSV). The insects were screened as potential natural carriers of Mr NV and XSV. RT-PCR (reverse transcription polymerase chain reaction) analysis gave positive results for Mr NV and XSV in Belostoma sp., Aesohna sp., Cybister sp. and Notonecta sp., and negative results for Nepa sp. An Aedes albopict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 26 publications
0
29
0
1
Order By: Relevance
“…XSV and MrNV have been detected in aquatic insects of several species that were collected from nursery ponds containing freshwater prawn (Macrobrachium rosenbergii) infected with MrNV and XSV [89]. Both viruses could also replicate in mosquito cell lines, suggesting that aquatic insects serve as vectors for XSV and MrNV transfer [89]. Several XSV isolates from geographically remote locations, including the French West Indies, Thailand, Taiwan, China, and India, have been reported [10].…”
Section: Extra Small Virusmentioning
confidence: 96%
See 1 more Smart Citation
“…XSV and MrNV have been detected in aquatic insects of several species that were collected from nursery ponds containing freshwater prawn (Macrobrachium rosenbergii) infected with MrNV and XSV [89]. Both viruses could also replicate in mosquito cell lines, suggesting that aquatic insects serve as vectors for XSV and MrNV transfer [89]. Several XSV isolates from geographically remote locations, including the French West Indies, Thailand, Taiwan, China, and India, have been reported [10].…”
Section: Extra Small Virusmentioning
confidence: 96%
“…However, the exact relationship and the effect of XSV multiplication on that of MrNV remain obscure [10,107]. XSV and MrNV have been detected in aquatic insects of several species that were collected from nursery ponds containing freshwater prawn (Macrobrachium rosenbergii) infected with MrNV and XSV [89]. Both viruses could also replicate in mosquito cell lines, suggesting that aquatic insects serve as vectors for XSV and MrNV transfer [89].…”
Section: Extra Small Virusmentioning
confidence: 97%
“…By contrast, Sudhakaran et al (2007) recently reported the successful propagation of Macrobrachium rosesnbergii nodavirus (MrNV) and extra small virus (XSV) in C6/36 cells by serial passaging of the culture supernatant. This is probably an exceptional case, since these viruses have also been shown to infect insects naturally (Sudhakaran et al, 2008).…”
mentioning
confidence: 96%
“…Of particular importance for this list would be viral pathogens such as Macrobrachium rosenbergii nodavirus (MrNV) and extra small virus (XSV) that are causally related to white tail disease , Sahul Hameed et al 2004, Bonami et al 2005, Yoganandhan et al 2006) and result in severe mortality in hatcheries. These viruses may be transmitted vertically from naturally infected broodstock to larvae (Sudhakaran et al 2007) or via reservoir carriers that may include other shrimp (Sudhakaran et al 2006a,b) or even aquatic insects (Sudhakaran et al 2008). The only other virus reported from natural infections of M. rosenbergii is similar to the one known as hepatopancreatic parvovirus (HPV) in penaeid shrimp (Anderson et al 1990, Lightner et al 1994) based on histopathology (Bonami et al 1995, Lightner 1996.…”
Section: Introductionmentioning
confidence: 99%